The influence of customer interaction in virtual brand community on brand loyalty - Adzharuddin, Nor Azura; Xiaomeng, Li (Human Resource Management Academic Research Society, 2023)
Purpose - The main purpose of this study is to determine the relationship among the customer interaction and brand loyalty of virtual brand communities through the uses and gratification theory (UGT), this research mainly answer some research questions, a) the level of customer interaction in virtual brand community; b) the level of brand loyalty in virtual brand community; c) the relationship between the customer interaction and brand loyalty in virtual brand community. Design/methodology - This study chooses several different virtual brand communities established on different social platforms as the research objects, and studies their customer interaction and brand loyalty. Findings - This study divides the interaction into three dimensions: product information interaction, interpersonal emotional interaction and self-identity interaction, chooses virtual brand member interaction as independent variables, and constructs a theoretical model of brand member interaction based on the use satisfaction theory (UGT) and social identity theory. Practice implication - Brand community managers can draw on the results of this study and formulate corresponding strategies to improve customer loyalty to the brand.